Activity of Ethyl Acetate Fraction of Merremia mammosa Hall as Anti-Influenza A (H1N1) - Neny Purwitasari1 , Mangestuti Agil2 , Herra Studiawan3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The outbreak of influenza A viruses (H1N1 and H5N1) has raised a global concern on the future risk of a pandemic. Oseltamivir, the current neuraminidase inhibitor, could not meet the demand if there is a major outbreak. Thus, there is a need to find alternative treatment for influenza A, especially from natural herbs. The objectives of this study were to determine antiviral influenza A activities of Merremia mammosa Hall against influenza A H1N1. People in Madura island, Indonesia used this rhizome to cure tuberculosis. In this research, Merremia mammosa Hall rhizome was extracted gradually using n-hexane to remove the non-polar compound. The residue was extracted using ethyl acetate to obtain semi-polar extract. The ethyl acetate fraction of Merremia mammosa Hall was subjected to in vitro antiviral assay against influenza A (H1N1) virus using Hemagglutinin Assay. This is a method for titering influenza viruses based their ability to attach molecules present on the surface of chicken red blood cell. The virus was incubated in embryonated chicken eggs and treated by ethyl acetate fraction of M. mammosa for 3 x 24 hours. Allantoic fluid was harvested and subjected on hemagglutinin assay to measure the titre of virus after treated with the fraction. The ethyl acetate extract of Merremia mammosa Hall can reduce the titer of hemagglutinin virus by 97.39% at concentration 1000 µg/mL In conclusion, Merremia mammosa Hall has the potential to be developed as agent of antiinfluenza A infection.